Gender differences in the response to decision power and responsibility: Framing effects in a dictator game - Lisa Bruttel; Florian Stolley (Games, 2018)
This paper studies the effects of two different frames on decisions in a dictator game. Before making their allocation decision, dictators read a short text. Depending on the treatment, the text either emphasizes their decision power and freedom of choice or it stresses their responsibility for the receiver's payoff. Including a control treatment without such a text, three treatments are conducted with a total of 207 dictators. Our results show a different reaction to these texts depending on the dictator's gender. We find that only men react positively to a text that stresses their responsibility for the receiver, while only women seem to react positively to a text that emphasizes their decision power and freedom of choice.
Keywords: C91; D63; D64; D91; 330; dictator game; framing; gender; experiment